2001
DOI: 10.1046/j.1365-3091.2001.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpycnal plume formation from riverine outflows with small sediment concentrations

Abstract: A series of laboratory experiments has been conducted in order to elucidate the sediment‐induced mixing processes accompanying riverine outflows; specifically, the discharge of a warm, fresh, particle‐laden fluid over a relatively dense, cool brine. In a parameter regime analogous to recently acquired field measurements, hypopycnal (surface) plumes were subject to a convective instability driven by some combination of heat diffusing out of the warm, fresh, sediment‐laden plume and particle settling within it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
249
2
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 288 publications
(272 citation statements)
references
References 35 publications
15
249
2
6
Order By: Relevance
“…This produces an unstable band of sediment-laden saltwater, i.e., the so-called interface layer, sitting between the muddy freshwater and the underlying clear saltwater. This phenomenon has been experimentally observed by Hoyal et al [1999b], Parsons et al [2001], and Blanchette and Bush [2005] and examined through linear stability analysis by Burns and Meiburg [2012] and Yu et al [2013] and Direct Numerical Simulation (DNS) by Yu et al [2014] and Burns and Meiburg [2015]. A few defining characteristics of the settlingdriven mechanism are the general creation of the interface layer below the initial stratification contact [Hoyal et al, 1999b], the onset of Rayleigh-Taylor generated plume like structures, asymmetry in the downward and upward interface motions, and the overall larger length scales of the instabilities and instabilities spacing (centimeter scale) compared to the double-diffusive generated fingering (millimeter scale) [Hoyal et al, 1999b;Blanchette and Bush, 2005;Burns and Meiburg, 2012;Yu et al, 2013;Burns and Meiburg, 2015;Yu et al, 2014].…”
Section: Interface Instabilities In the Absence Of Turbulent Mixingsupporting
confidence: 60%
See 4 more Smart Citations
“…This produces an unstable band of sediment-laden saltwater, i.e., the so-called interface layer, sitting between the muddy freshwater and the underlying clear saltwater. This phenomenon has been experimentally observed by Hoyal et al [1999b], Parsons et al [2001], and Blanchette and Bush [2005] and examined through linear stability analysis by Burns and Meiburg [2012] and Yu et al [2013] and Direct Numerical Simulation (DNS) by Yu et al [2014] and Burns and Meiburg [2015]. A few defining characteristics of the settlingdriven mechanism are the general creation of the interface layer below the initial stratification contact [Hoyal et al, 1999b], the onset of Rayleigh-Taylor generated plume like structures, asymmetry in the downward and upward interface motions, and the overall larger length scales of the instabilities and instabilities spacing (centimeter scale) compared to the double-diffusive generated fingering (millimeter scale) [Hoyal et al, 1999b;Blanchette and Bush, 2005;Burns and Meiburg, 2012;Yu et al, 2013;Burns and Meiburg, 2015;Yu et al, 2014].…”
Section: Interface Instabilities In the Absence Of Turbulent Mixingsupporting
confidence: 60%
“…The primary outcome of the study was a phase diagram depicting the dominate instability mode as a function of a thermal stabilizing ratio and sediment concentration. Parsons et al [2001] similarly concluded that thermal stratification and high sediment concentrations are likely needed for double diffusion to dominate. In addition, they identified an instability that is different than classic double-diffusive fingering.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
See 3 more Smart Citations